"Identificaciòn del perfil fenólico del mucílago y cascarilla de cacao (Theobroma cacao L.) de las variedades CCN-51 y Nacional". - Arreaga Chevez, Adner Alejandro (2020)
Cocoa production in Ecuador is considered one of the most important items; presenting a high difference in relation to other export products. This fruit is cultivated, harvested and commercialized with great continuity, generating a large amount of waste such as ears, exudate, placenta and husk. The identification of the phenolic profile of the mucilage and cocoa husk samples was carried out by High Resolution Liquid Chromatography (HPLC); being Procyanidins B1............................................................. ,